Generic medications in ophthalmology. Issue 3 (9th November 2012) - Zore, Matt; Harris, Alon; Tobe, Leslie Abrams; Siesky, Brent; Januleviciene, Ingrida; Behzadi, Jennifer; Amireskandari, Annahita; Egan, Patrick; Garff, Kevin; Wirostko, Barbara
Abstract : The purpose of this review is to discuss the process of genericisation of medications in the US and Europe with a focus on ophthalmic drugs. Regulatory guidelines of the US Food and Drug Administration and the European Medicines Agency will be discussed, and the advantages and concerns of genericisation will be explored. We will look at various studies concerning the safety and efficacy of generic drugs compared to their branded counterparts. In particular, the challenges of assuring bioequivalence and therapeutic equivalence in topical ophthalmic drugs will be examined.